Corporate sustainability and financial performance: Collective reputation as moderator of the relationship between environmental performance and firm market value. (10th December 2020) - Kim, Seonghoon; Terlaak, Ann; Potoski, Matthew
Abstract: Markets value superior corporate sustainability performance in part because investors use a firm's environmental performance as a signal of desirable but difficult‐to‐observe attributes, such as the firm's integrity capacity. Yet a signaling conflict can arise when a firm belongs to an organizational form that has a collective reputation for being unethical. In such circumstances, the firm's environmental performance may no longer credibly signal its underlying integrity capacity, leading markets to adjust downward the value they would otherwise place on the firm's environmental performance. Using longitudinal data on South Korean firms, we find that improvements in firm environmental performance lead to smaller increases in market values for firms belonging to a poorly reputed organizational form. However, firms can partially recover lost value by adopting firm features that reduce the signaling conflict, thereby restoring the notion of corporate sustainability performance driving firm market values.